Effect of C on the Martensitic Transformation in Fe-C Alloys in the Presence of Pre-Existing Defects: A Molecular Dynamics Study - Karewar, Shivraj; Sietsma, Jilt; Santofimia, Maria J. (Crystals, 2019)
Molecular dynamics simulations are used to investigate the atomic effects of carbon (C) addition in Fe on the martensitic phase transformation in the presence of pre-existing defects such as stacking faults and twin boundaries. The pre-existing defect structures in Fe-C alloys have the same effect on the atomistic mechanisms of martensitic transformation as in pure Fe. However, C addition decreases the martensitic transformation temperature. This effect is captured by characterizing three parameters at the atomic level: atomic shear stresses, atomic energy, and total energy as a function of temperature for face-centered-cubic (fcc) and body-centered-cubic (bcc) phases. The thermodynamic effect of fcc phase stabilization by C addition is revealed by the atomic energy at a particular temperature and total energy as a function of temperature. The barrier for fcc-to-bcc transformation is revealed by analysis of atomic shear stresses. The analysis indicates that addition of C increases the atomic shear stresses for atomic displacements during martensitic transformation, which in turn decreases the martensitic transformation temperature.
CRIS-Team WoS Importer:2019-03-26

On the influence of Al-concentration on the fracture toughness of NiAl: Microcantilever fracture tests and atomistic simulations - Webler, Ralf; Baranova, Polina; Karewar, Shivraj; Möller, Johannes; Neumeier, Steffen; Göken, Mathias; Bitzek, Erik (Acta Materialia, 2022)
While the mechanical properties of the stoichiometric B2 β-phase of NiAl are well established, the effect of off-stoichiometric composition on the fracture behavior has not yet been systematically studied over the entire composition range of 40-55% Al. Here we use microbending tests on notched cantilever beams FIB-milled from NiAl single crystals with an aluminized as well as an oxidation-induced composition gradient to determine the influence of the Al concentration on the fracture toughness. Small variations from the stoichiometric composition are shown to lead to drastic changes in fracture behavior. Ni-rich NiAl shows a gradual decrease of fracture toughness and plastic energy dissipation with Ni-concentration that follows the inverse proportionality to the yield stress postulated by the Ritchie, Knott and Rice (RKR) model. Al-rich NiAl, however, shows a concentration-independent low fracture toughness and no signs of accompanying plasticity - both which can not be described by the RKR model. Detailed atomistic simulations show that rather than affecting the theoretical fracture toughness according to the thermodynamic Griffith criterion, structural vacancies in Al-rich NiAl lower the kinetic barrier for crack propagation, explaining the observed different concentration dependence of the fracture toughness. Similar observations are also expected for fracture in other off-stoichiometric B2 aluminides.
CRIS-Team Scopus Importer:2022-06-10
Keywords: Atomistic simulation; Fracture; Intermetallics; Micro cantilever bending; NiAl